基于偏态接触表面粗糙度的纸基摩擦材料湿式制动器啮合特性研究 - 罗天洪; 李富盈; 李春宏; 黄兴刚; 朱孙科; 胡启国 (Jixie chuandong)
In order to enhance and improve the braking characteristic of WetMultiple of Disc Brake（WMDB）,the WMDB of mining engineering truck drive axle is considered as research object.For contact surface skewness and roughness property of paper-based friction material,through comparing the Weibull and Gaussian asperity distribution,the new,run-in and Glazed material friction coefficient variation law and brake meshing characteristic are researched.The results indicate that asperity contact pressure model usingWeibull distribution had a better analysis effect than using Gaussian distribution and Weibull distribution forecast brake meshing time is also longer than using Gaussian distribution.As calculated by the contactsurface skewness and usingWeibull distribution.Itis found thatin the initial stages of brake meshing,a brake torque fluctuation exists to be the main reason for the braking stick-slip vibration.The coefficientof friction-speed curve with a positive slope can reduce the increase of brake torque during the end of the brake meshing.By addingmaterial skewness and roughness of the contact surface features in the calculation model and combiningwith asperity body Weibull distribution,it shows that calculate resultswith the test results conform to be a high degree.